Construction feasibility evaluation for potential ecological corridors under different widths: a case study of Chengdu in China - Xie, Yusong; Wang, Qianna; Xie, Mengqing; Shibata, Shozo (Landscape and ecological engineering, 2023)
Accelerating urbanization has led to the shrinkage of natural habitats, intensification of landscape fragmentation, reduction of cropland and forest areas, and degradation of biodiversity. Against this background, considering ecological corridors are important linear structures connected to habitat patches, helping enhance urban ecological resilience and protect biodiversity. A growing number of studies focus on identifying potential ecological corridors and evaluating the relative importance of such corridors on the effects of connected habitat patches. However, in the evaluation process, previous studies ignored the linear structures of corridors, and did not explore the internal characteristics differences under different corridor widths. Accordingly, this study used the minimum cumulative resistance model (MCRM) to identify potential ecological corridors. After that, we designed the construction feasibility evaluation system for evaluating the relative importance of such corridors with different widths, and applied it to the rapidly expanding city of Chengdu in western China. The results show that internal characteristics of potential ecological corridors vary significantly under different widths. Using the construction feasibility evaluation system, we found that more than 75% of the identified potential ecological corridors are difficult to construct. The construction sequence has obvious differences under different widths, besides providing a reference for construction and selecting widths for potential corridors in Chengdu. This research highlights the importance of width selection in corridor evaluation. The construction feasibility evaluation provided reference information on identification, analysis, construction sequence, and construction practices for urban ecological network spatial planning.